Pseudomonas cepacia mutants blocked in the direct oxidative pathway of glucose degradation. - Lessie, T G (1979)
Glucose dehydrogenase-deficient strains of Pseudomonas cepacia grew normally with glucose as carbon source, indicating that the direct pathway of glucose oxidation does not play an essential role in this bacterium.